Construction of upper and lower complete denture using CAD/CAM technology - Dénes Palaszkó; János Kőnig; Judit Borbély; Péter Hermann; Szandra Körmendi (Hungarian Dental Association, 2022)
Successful treatment of complete edentulousness remains a great challenge for dentists and dental technicians. The digital revolution that stormed through dentistry, especially in fixed and implant prosthodontics, has not really penetrated the field of removable prosthodontics, especially not the treatment of complete edentulousness. Concerning these types of dentures, it is obvious that the developments in digital imaging are not able to substitute specific functional advantages of taking conventional impression, which is able to capture the moving mucosa. Different full-face scan- and CT images may be appropriate to record the position of patient's jaws; however, the availability, the simplicity of use, and the slowness of the software prevents such devices from being more commonly used. For now, we are able to digitally record all the information gained by the previously used methods; thus, these working methods supplement one another. The opportunities provided by the digital technology can be successfully used if we are ready to accept their limitations and are able to utilise them appropriately, so that it aids the patient. The technology is ready and profitable enough to provide a new option in treating patients with edentulousness, e.i. using 3D printing and milling, we are able to create such aesthetic and reproducible permanent dental fittings than never before.